Biscoitos tipo cookie isentos de glúten enriquecidos com Spirulina platensis e óleo de chia - Mattana, Ademir (2023)
In the last decade there has been an increase in the consumption of gluten-free cookies and cereals, as they serve not only clinically diagnosed celiac patients, but also consumers seeking to reduce or even exclude gluten from their diet. Thus, this work aimed to prepare gluten-free cookies, enriched with Spirulina platensis and chia oil, using brown rice flour to replace wheat flour. A complete 22 factorial design was applied to define the proportions of Spirulina platensis (SP) and chia oil (OC) to be added to the different cookie formulations. Seven tests were obtained from the addition of SP (2 to 8 g/100 g of brown rice flour) and OC (10 to 25 g/100 g of brown rice flour), designated as F1 to F7. In addition to these, a standard formulation (FP) was developed. The proximate composition, physicochemical properties, texture and fatty acid profile, microbiological quality and sensory evaluation were characterized. For proximate composition and physicochemical analyzes the values ranged from 4.39 to 6.33% for moisture, from 2.30 to 2.72% for ash, from 5.12 to 9.31% for proteins, from 11.02 to 17.99% for lipids, 66.68 to 73.04% for carbohydrates, 6.80 to 7.03 for pH and 58.27 to 62.41 for total color difference (ΔE). Water activity showed no significant difference (p<0.05) between formulations F1 to F7, with an average result of 0.2500. In the texture profile, the hardness parameter presented values ranging from 8.49 to 25.95 kgf, while fracturability varied from 6.72 to 8.96 mm, with no significant difference (p<0.05) between the formulations. Therefore, the proximate composition, physicalchemical properties and texture profile remained in accordance with technological aspects for biscuit development. In the fatty acid profile, it was found that F3 (2% Spirulina and 25% chia oil) presented a higher total content of polyunsaturated fatty acids (11519.74 mg 100 g-1 of sample), differing significantly of the other formulations (p<0.05), which is important because polyunsaturated fatty acids help reduce the risk of diseases, in addition to improving the functional characteristics of foods by providing fatty acids. The thrombogenic (TI) and atherogenic (AI) indices were 0.08 to 0.13 and 0.11 to 0.16 respectively, values considered adequate for the prevention of coronary heart disease. In relation to the sensorial attributes of appearance, color, flavor, texture and overall impression evaluated, it was possible to observe that F3 showed greater acceptance compared to the other formulations. It was found that the lowest acceptance rates for all sensorial attributes evaluated were for the tests with the highest concentration of SP (F4 and F5). In relation to the overall impression, the three formulations presented values above 70%, admitted as a minimum percentage of acceptability index. The results indicate that the addition of SP (2%) and OC (25%) can be an alternative to increase the content of proteins and polyunsaturated fatty acids in cookie-type biscuits, and presents technological potential for application in bakery products.